أهمية نظام الرقابة الداخلية في تحسين أداء المؤسسة دراسة حالة: الشركة الجزائرية للكهرباء والغاز-مديرية التوزيع بالوادي- خلال الفـتـــــرة: (2019 -2020-2021) - سعد, كروش; يوسف, تليلي; ميلود, تريعة (unuversity of eloued- جامعة الوادي, 2023)
"تهــــدف الدراســــة إلى توضيح أهمية نظام الرقابة الداخلية في تحسين أداء للمؤسسة، وذلك من خلال التطرق إلى جميع المفاهيم والمتغيرات المحيطة بمصطلح نظام الرقابة الداخلية وأداء المؤسسة وآليات تحسينه. كما تم الاعتماد على المنهج الوصفي في الجانب النظري، والتحليلي في الجانب التطبيقي باستخدام دراسة الحالة على الشركة الجزائرية للكهرباء والغاز- مديرية التوزيع بالوادي-خلال فترة (2019-2020-2021)، من خلال استخدام المقابلة والملاحظة ووثائق مقدمة من المؤسسة (القوائم المالية المتمثلة في الميزانية وجدول حسابات النتائج)، حيث تم تحليل الوضعية المالية باستخدام مؤشرات التوازن المالي والنسب المالية. ومن خلال نتائج الدراسة المتوصل إليها، ان تطبيق نظام الرقابة الداخلية يحظى بأهمية كبيرة، ويعتبر أداة من أدوات الإدارة، تساعد في اتخاذ القرارات، وتحسين الأداء المالي للمؤسسة، ويضمن تطبيق الإجراءات والقوانين الإدارية، وكذلك اعطاء صورة عن الوضعية المالية للمؤسسة عن طريق تحليل النسب المالية ومؤشرات التوازن المالي. وقد تم تقديم التوصيات والاقتراحات اللازمة من أجل تحسين الأداء المالي للمؤسسة محل الدراسة. " "The study aims at clarifying the importance of Internal Control in improving the Performance of enterprises by addressing all the concepts and variables surrounding the concept of Internal Control, the performance of the enterprise and the improvement of its mechanisms. The study was based on the Descriptive Approach in its theoretical chapters and the Analytical Approach in the practical chapter, utilizing a case study applied on the Algerian Electricity and Gas Company – El-Oued’s Distribution Directorate during the following periods (2019/2020/2021)- through the use of the interview, observation and documents submitted by the company (Financial lists of budget and results calculations table). Financial situation was analyzed using financial balance indicators and financial ratios. Through the results of the study, the application of the Internal Control system is of great importance and is considered one of the management tools that helps in making decisions and improving the financial performance of the enterprise, ensures the application of administrative procedures and laws, and affords a picture of the financial situation of the enterprise by analyzing financial ratios and financial balance indicators. The necessary recommendations and suggestions were made in order to improve the financial performance of the institution under consideration. "
Keywords: نظام الرقابة الداخلية، أداء المؤسسة، آليات تحسين الأداء المالي; enterprise performance – financial performance improvement mechanisms - Internal Control System -